ANALYSIS OF NATIONAL PRIVATE BANK MARKETING MANAGEMENT STRATEGIES IN AN EFFORTS TO ATTRACT FUNDS FROM THE COMMUNITY - Ruby Santamoko (Adisam Publisher, 2024)
Marketing strategy is a planned and structured marketing procedure that will be carried out to achieve company goals. As a company develops, company competition cannot be avoided, especially in the banking world. To implement the right and best marketing strategy, one way is for the company to look at the service quality and value of the services provided to consumers. This is important because marketing is carried out in order to fulfill consumers' needs and desires for a product/service. Marketing can also be done in order to face competitors who are increasing over time. Professional marketing management is needed to meet the needs and desires of customers. Banking marketing strategies must be adapted to the bank's external and internal environmental conditions, as well as the bank's resources and capabilities. Therefore, there are several points in the marketing strategy at this bank that can be explained, namely product strategy, price strategy, location and layout strategy, promotion strategy.